2022
DOI: 10.1002/joc.7596
|View full text |Cite
|
Sign up to set email alerts
|

Increased amplitude of the North Pacific Gyre Oscillation towards recent: Evidence from tree‐ring‐based reconstruction since 1596

Abstract: The North Pacific Gyre Oscillation (NPGO) is the second leading mode of the sea surface height (SSH) of the North Pacific Ocean, playing a key role in causing regional ecosystem changes and large-scale climate anomalies. However, its longterm evolution prior to the industrial era is largely unknown. This study provides a reconstruction of the NPGO from 1596 onwards from 19 NPGO-sensitive treering chronologies in the Himalayan Mountains, the Rocky Mountains, the Coastal Mountains and the Alaskan Mountain Range,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Additionally, several previous studies have suggested that the higher frequency of CPW climate variability due to anthropogenic warming may enhance NPGO variability and strengthen the linkage between them [50,51] . As shown in Fig.…”
Section: Coral-based Npgo/vm Variability Reconstruction Back To the 1...mentioning
confidence: 95%
See 3 more Smart Citations
“…Additionally, several previous studies have suggested that the higher frequency of CPW climate variability due to anthropogenic warming may enhance NPGO variability and strengthen the linkage between them [50,51] . As shown in Fig.…”
Section: Coral-based Npgo/vm Variability Reconstruction Back To the 1...mentioning
confidence: 95%
“…There are some proxy-based NPGO reconstructions (tree-ring-based [51,55] and corals-based [26][27][28] ); however, the origins of the records are primarily centred in the central tropical Paci c and eastern Paci c. Our study is the rst longterm reconstruction of the NPGO/VM variability derived from the NWP reef-building coral skeleton archive, dating back to the 19th century. Sanchez et al [28] reported decadal NPGO variability from coral skeletal δ 18 O records from Clarion Island (in the eastern Paci c).…”
Section: Coral-based Npgo/vm Variability Reconstruction Back To the 1...mentioning
confidence: 99%
See 2 more Smart Citations
“…This means that the NPGO can influence WNP RI activity on shorter timescales than the PDO. Third, the variance and amplitude of the NPGO have increased since 1950, and are generally comparable to the PDO (Litzow et al 2020, Dong et al 2022. The fraction of Pacific SST variability contributed by the NPGO has increased, with the NPGO surpassing the PDO as the dominant mode of North Pacific SST variability since the 1990 s (Bond et al 2003, Litzow et al 2020.…”
Section: Introductionmentioning
confidence: 94%